2012
DOI: 10.1002/adma.201201841
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional Electrolyte‐Gated Organic Field‐Effect Transistors

Abstract: The surface modification of solution-gated organic field-effect transistors is investigated. The introduction of different surface groups leads to a control of the pH sensitivity, determined by the pKa value of the added surface moiety. Together with the successful demonstration of enzyme modification of the surface, this work reveals the large potential of organic SGFETs for biosensor applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 38 publications
5
100
0
Order By: Relevance
“…We therefore tested both types of ZnO films in TFTs gated by phosphate-buffered saline (PBS) as an aqueous gate medium. PBS is often used to simulate bodily fluids [2][3][4] and is thus a realistic medium for biosensor applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore tested both types of ZnO films in TFTs gated by phosphate-buffered saline (PBS) as an aqueous gate medium. PBS is often used to simulate bodily fluids [2][3][4] and is thus a realistic medium for biosensor applications.…”
Section: Resultsmentioning
confidence: 99%
“…TFT devices gated by a biologically realistic aqueous electrolyte, phosphate-buffered saline (PBS) solution, were sensitised (e.g. by enzymes) either at the semiconductor/water interface [2,3], or at the gate electrode [4]. The latter is easier and more versatile as it requires no chemical modification of the semiconductor, which can lead to loss of performance.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, there is a tremendous activity to explore organic semiconducting materials because they can be processed from solution at low temperature [1][2][3][4][5][6][7][8] hence, traditional printing technologies can be adapted to manufacture printed sensors and detectors. Such types of devices represent an important corner stone for applications such as distributed monitoring and medical surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Stille coupling is catalysed by the organometallic Pd(0) complex tris(dibenzylideneacetone)dipalladium(0), Pd 2 (dba) 3 [6]. Sensitisers used in PVC membranes typically also are organic metal-complexing agents at low concentration [12,13], including the membrane used by List-Kratochvil et al [5] which is described in [14].…”
Section: Discussionmentioning
confidence: 99%
“…Since then a number of water-gated organic TFTs (OTFTs) have been demonstrated that respond selectively to water-borne analytes due to specific sensitisers that were introduced into the transistor architecture [2,3]. This provides an alternative to the traditional ion-sensitive field between semiconductor and water-borne analyte [4] Of particular interest to the present work is the report by List-Kratochvil et al on a water-gated transistor that is sensitised for the selective detection of Na + ions with an ion-selective PVC membrane [5].…”
Section: Introductionmentioning
confidence: 99%